Learning Activity at SMP Muhammadiyah 5 Tulangan During Pandemic Covid 19 - Rani Syahda Hanifa; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The author carried out this research activity aimed to find how learning activities during the Covid 19 pandemic, especially with existence of government regulations regarding online learning. This research method uses qualitative methods and author directly conducts interviews with counseling guidance teachers. This research was conducted with object of Junior High School where the main focus of learning in junior high school in addition to learning theory, it’s important to build the character of students. Because when study in junior high school, psychologically they will naturally look for their respective identities so that their future consolidation will greatly affect how their environment is when studying in junior high school. However, how the efforts of an educational institution to optimize this and only through online media will be explained in more detail but concisely, concisely and clearly. Each school will have a certain culture that is tailored to the vision of the school. According to the results of research conducted by author,level of junior high school learners in the area, the teacher has carried out the learning as effectively and optimally as possible. The school also uses its authority wisely that offline learning activities will not start if there is no approval from the student's guardian. The focus point of developing the character of students here is regarding the foundation of the Islamic religion, although learning activities are carried out online, these values are maintained as much as possible by SMP Muhammadiyah 5 Tulangan, in accordance with institution that houses the school, religious values become a major milestone in cultivating participant character students.